Implementation of Human Resources Management According to a Good Governance Perspective in Indonesia - Budi Rismayadi (SEAN Institute, 2024)
Good governance is the main basis for implementing government policies, including HR management, in order to achieve optimal efficiency, transparency and accountability. This research aims to investigate the implementation of human resource management (HR) based on a good governance perspective in Indonesia. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of good human resource management (HR) by practicing the principles of good governance has a positive impact on government administration. By implementing a transparent selection process, continuous training, and fair performance evaluation, organizations can build quality and skilled Human Resources. Fair welfare policies and structured career development opportunities also contribute significantly to employee satisfaction and increased productivity. In addition, instilling good governance values in organizational culture through employee involvement in decision making and an emphasis on work ethics increases organizational integrity and transparency. In conclusion, good HR management is the foundation for achieving good governance, producing responsive and high quality public services to the community.